2015
DOI: 10.1111/1365-2745.12428
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale hydrological niche differentiation through the lens of multi‐species co‐occurrence models

Abstract: Summary1. Theory suggests spatial heterogeneity can facilitate species co-occurrence at fine scales, but environmental data are rarely collected at sufficiently high resolution to test this empirically. Whilst there is emerging evidence that subtle variation in soil hydrology represents a fundamental fine-scale niche axis within plant communities, this is largely derived from studies of soil hydrology in isolation from other environmental factors. 2. We assessed the comparative importance of fine-scale hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 50 publications
0
38
2
1
Order By: Relevance
“…Interestingly, for the LV model we found that the number of LVs needed to estimate the species correlation matrix adequately was substantially larger than previously suggested (Letten et al. , Warton et al. ), regardless of whether the model did or did not contain a detection component.…”
Section: Discussioncontrasting
confidence: 58%
“…Interestingly, for the LV model we found that the number of LVs needed to estimate the species correlation matrix adequately was substantially larger than previously suggested (Letten et al. , Warton et al. ), regardless of whether the model did or did not contain a detection component.…”
Section: Discussioncontrasting
confidence: 58%
“…One possible way for evaluating potential effects of niche sharing is to use new lines of statistical methods, which divide effects of direct interspecific interactions from those of shared environmental preferences [7678]. Although these methods have been used to analyze data collected in observational community ecological studies, our preliminary analysis on human gut microbiome datasets [79] has shown that the new statistical approach is applicable to high-throughput sequencing-based datasets if data of physical/chemical environmental conditions are available (Toju et al, in review).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recognized importance of scale, studies determining its effects on plant community heterogeneity are uncommon (Steinberg & Kareiva 1997). Although the focus of our study was the effect of time since fire on vegetation variables, it should also be noted that environmental heterogeneity can promote niche partitioning and provide opportunities for local-scale species coexistence; however, this is conditional upon the scale at which the community is sampled (Letten et al 2015). This pattern is predominantly due to the fact that larger samples are more likely to include a greater subset of species from a given community, thus, increasing the level of similarity among quadrats, compared with smaller quadrats (Collins 1992).…”
Section: Discussionmentioning
confidence: 98%